The Strength Index of Short and Slender Circular Concrete-Filled Steel Tube Columns - Hana Hasnan, Nurul; Hamid, Roszilah; Aminah Osman, Siti (International Journal of Engineering and Technology, 2019)
The factors affecting the sectional capacity, also known as strength index (SI) of concrete-filled steel tube columns (CFSTC) are, among others, type of cross-section and slenderness ratio (L/D). This study is to determine the effects of slenderness ratio of short (L/D  3.4) and slender (L/D  10) circular CFSTC on the SI. Concentric load tests were conducted to determine the ultimate strength (Nue) of ten circular sections of short and slender CFSTC with ordinary Portland cement concrete (OPCC) and pozzolan concrete (PC) infills. The SI are determined using several design codes. Results show that the SI for short CFSTC is higher than the slender for circular section. This is because of the effect of the L/D of short and slender CFSTC circular section. It shows that the composite action between steel tube and core concrete for short is more efficient than slender circular columns. The results also show that similar compressive strength concrete (fcu) infills, either comprises of OPCC or PC do not affect the the SI values. Different design codes provide different concrete confinement safety coefficients thus the difference in the SI values. AISC (LRFD) provides the highest SI for both short and slender CFSTC. Whereas, EC4 and AS5100.6 provide the lowest SI for short and AIJ provides lowest SI for slender circular sections. The lowest calculated values of SI show the most efficient design of composite column.
Keywords: Concentric load; high strength concrete; stress-strain; structural behaviours; ultimate strengths.